Atypical mycotic lesion in the guttural pouch of a Thoroughbred race horse - Yiew, Xiu Ting; Khairuddin, Nurul Hayah; Murdoch, Alistair Ivon King; Patil, P. V.; Singam, Reza Sashi; Koay, Chin Peng (Veterinary Association Malaysia, 2015)
A six-year-old Thoroughbred race horse was presented with left unilateral mucopurulent nasal discharge. Endoscopic examination revealed atypical mycotic lesion within the guttural pouch in which the fungal mass was not located on any neurovascular structures. This case was successfully treated by the combination of manual debulking of fungal diphtheritic plaques and medical treatment that included daily local irrigation and systemic medication. There were no complications and the horse returned to race three weeks later.